Transcriptional profiling of the Arabidopsis abscission mutant hae hsl2 by RNA-Seq - Niederhuth, Chad E (BioMed Central, 2013)
BACKGROUND: Abscission is a mechanism by which plants shed entire organs in response to both developmental and environmental signals. Arabidopsis thaliana, in which only the floral organs abscise, has been used extensively to study the genetic, molecular and cellular processes controlling abscission. Abscission in Arabidopsis requires two genes that encode functionally redundant receptor-like protein kinases, HAESA (HAE) and HAESA-LIKE 2 (HSL2). Double hae hsl2 mutant plants fail to abscise their floral organs at any stage of floral development and maturation. RESULTS: Using RNA-Seq, we compare the transcriptomes of wild-type and hae hsl2 stage 15 flowers, using the floral receptacle which is enriched for abscission zone cells. 2034 genes were differentially expressed with a False Discovery Rate adjusted p < 0.05, of which 349 had two fold or greater change in expression. Differentially expressed genes were enriched for hydrolytic, cell wall modifying, and defense related genes. Testing several of the differentially expressed genes in INFLORESCENCE DEFICIENT IN ABSCISSION (ida) mutants shows that many of the same genes are co-regulated by IDA and HAE HSL2 and support the role of IDA in the HAE and HSL2 signaling pathway. Comparison to microarray data from stamen abscission zones show distinct patterns of expression of genes that are dependent on HAE HSL2 and reveal HAE HSL2- independent pathways. CONCLUSION: HAE HSL2-dependent and HAE HSL2-independent changes in genes expression are required for abscission. HAE and HSL2 affect the expression of cell wall modifying and defense related genes necessary for abscission. The HAE HSL2-independent genes also appear to have roles in abscission and additionally are involved in processes such as hormonal signaling, senescence and callose deposition.